Extended program notes from a Master’s Recital of songs by Joaquín Turina, Jake Heggie, Emile Paladilhe and Johannes Brahms - Melton, John Christopher Jr. (My University, 2025)
This report contains information and analysis on the repertoire and ultimate performance of the vocal recital of Master’s Candidate, Chris Melton. The chapters are delineated by composer and relate a brief biography and some musical analysis from the author. The selected repertoire consists of Poema en forma de canciones by Joaquín Turina, Of laughter and farewell by Jake Heggie, and select songs by Johannes Brahms and Émile Paladilhe.
Keywords: Song; Johannes Brahms; Joaquín Turina; Emile Paldilhe; Mozart; Jake Heggie; Opera; Tenor; Singing; Music performance